Pharmacoeconomic Analysis of Asthma in Pediatric Patients in Tertiary Care Hospital in Kerala - J, Stejin; KV, Kishor; KN, Nandha; A, Srinivasan; PKC, Arul; S, Kannan (Indian Journal of Pharmacy Practice)
Bronchial asthma is the most common chronic disease of childhood, responsible for a significant proportion of the abstinence from school. The objective of our study was to determine the total direct and indirect cost of asthma in pediatrics. The study design was prospective observational study. This study was carried out among the pediatrics aged (0-15), and a total of 158 patients were taken. Aquestionnaire is prepared based on GINA guidelines of asthma for data collection, the patients/caregivers are requested to answer the questionnaire. From 158 patients enrolled 110(70%) were males and 48(30%) were females. The direct cost of asthma was found to be 88.59% and indirect cost was found to be 11.4%. This study shows that the direct cost was very high as compared to indirect cost. The medication cost was found to be high 46.10% of total cost followed by hospitalization cost 30.14%. According to the degree of severity the moderate persistent asthma was found to be 39.49% of the total cost of asthma. Study revealed that the asthma hospitalization can be decreased as the inhalation therapy use increased.
Keywords: Asthma; Pharmacoeconomics; Direct cost; indirect cost